ANALISIS PERANAN INFORMASI AKUNTANSI DAN NON AKUNTANSI TERHADAP INITIAL RETURN SAHAM - Meihendri, Meihendri (Jurnal Benefita, 2016)
This study is aimed to examine the role effect of accounting information (firm size, Earning Per Share (EPS), Price Earning Ratio (PER), financial leverage and Return On Asset (ROA) and  non-accounting information (old shareholders, auditor reputation, underwriter reputation, age companies and types of industries) on initial stocks returns. This study used secondary data in the form of financial annual report that go public and listed on the Indonesian Stock Exchange in 2009-2013. The samples are 66 companies obtained through purposive sampling method. Then, hypothesis examination is done by using multiple linier regression analysis, before that firstly classical assumption test has been done. The result of this study showed that simultan  the variable accounting information and non-accounting information have an effect on initial stocks returns.  In partially  auditor reputation have an effect on initial stocks returns with a significant level of 5% and types of industries have an effect on initial stocks returns with a significant level of 10%. Based on the result in conclusion is the investor that will invest in company which are IPO need observe auditor reputation and types of industries in order to success acquiring initial stocks returns which are expectation. Keywords : Accounting Information, Non Accounting Information, Initial Return, IPO